Developing Cooperative Business Models for the Digital Era: A Workshop in Bekasi City - Santi Rimadias (Jurnal Pengabdian Pancasila (JPP), 2025)
This workshop aims to increase the capacity of cooperative managers in Bekasi City to develop innovative and sustainable business models in the digital era. This activity introduced the concept of Business Model Canvas (BMC) so that participants were able to design cooperative business models independently. With a participatory approach through interactive presentations and group discussions, the workshop was held on May 24, 2025, at the Metland Hotel, attended by 11 cooperative managers from various companies. As a result, participants gained practical knowledge and skills in compiling BMC-based digital business models. This activity shows an increase in awareness and readiness among cooperative managers to develop digital-based business models for organizational growth.